2020
DOI: 10.1017/s0029665120000762
|View full text |Cite
|
Sign up to set email alerts
|

Public acceptability of government interventions to reduce obesity: policy effectiveness, policy fairness, government trust and political ideology

Abstract: AbstractFrequent consumption of sugar-sweetened beverages (SSBs) has been linked to a greater risk of obesity, type 2 diabetes mellitus, dental caries and coronary heart disease. SSBs are an ideal target for public health intervention to help control the type 2 diabetes mellitus epidemics since they have absolutely no nutritional value, and do not protect against disease. However, successful implementation of policies to reduce consumption of SSBs depends on public acceptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…When comparing with the 2015 French study, we observed a slight increase in the proportion of the population who perceived the measure as useful (57•7 % in 2015 v. 60•2 % in 2021) and an important decrease in the proportion of the population who qualified the tax as unfair (49•3 % in 2015 v. 34•4 % in 2021). Perceived effectiveness and perceived fairness have been found to be positively associated with public acceptance (31) . The 2018 revision of the tax appeared to be an opportunity for the government to reframe the policy as a public health measure, and these changes may have further led to an increase in acceptance (32) .…”
Section: Discussionmentioning
confidence: 99%
“…When comparing with the 2015 French study, we observed a slight increase in the proportion of the population who perceived the measure as useful (57•7 % in 2015 v. 60•2 % in 2021) and an important decrease in the proportion of the population who qualified the tax as unfair (49•3 % in 2015 v. 34•4 % in 2021). Perceived effectiveness and perceived fairness have been found to be positively associated with public acceptance (31) . The 2018 revision of the tax appeared to be an opportunity for the government to reframe the policy as a public health measure, and these changes may have further led to an increase in acceptance (32) .…”
Section: Discussionmentioning
confidence: 99%
“…To whom people attribute control and responsibility for a certain event also depends on individual factors like political orientation. There is substantial empirical evidence across various decision-making contexts that political orientation needs attention in determining public-policy support (e.g., Gunarathne et al, 2020; Milner et al, 2019; Ramos et al, 2020; Yun et al, 2019). For instance, in a series of studies on the support for environmentally friendly airports, Milner et al (2019) found conservatives to be less supportive than liberals.…”
Section: An Integrative Public-policy-acceptance Frameworkmentioning
confidence: 99%
“…Teoh et al [22] predicted food waste prevention behavior by analyzing the impact of social media use on consumers' attitudes towards food waste. Gunarathne et al [23] also believe that the key to the successful implementation of intervention policies to reduce sugar drinks lies in public acceptance and support. Jabeen et al [24] used the theory of interpersonal behavior to explore the relationship between emotion and attitude and the individual's behavioral intention to reduce food waste.…”
Section: Introductionmentioning
confidence: 99%